Voluntourism as an Effort to Realize Sustainable Tourism to Reduce Waste in the Ocean - Janitra, Nabila Thyra; Muis, Afni Regita Cahyani (Global Strategis, 2023)
In response to the problem of increasing waste in the ocean, UNWTO formulated sustainable tourism to create economic, social, and environmental stability. In the effort to realize sustainable tourism, UNWTO introduces a voluntourism program that directly seek to attract tourists' interest and make tourists become aware of the importance of protecting the environment. This study aims to understand the voluntourism strategy to realize sustainable tourism to reduce waste in the ocean. The method used in this study is a qualitative-explorative method that intends to explore social phenomenon based on the variables that have been formulated. In responding to the issue of marine pollution caused by garbage, voluntourism makes various efforts to cooperate with several stakeholders. The voluntourism program that focuses on the topic of marine pollution is expected to become a policy recommendation to be implemented by various countries, hence efforts to reduce waste in the sea can be massively carried out in different parts of the world. This study discusses the distribution of waste in the oceans and efforts to handle it through voluntourism programs. Keywords: Ocean Waste, Sustainable Tourism, Voluntourism   Dalam merespon permasalahan peningkatan sampah di lautan, UNWTO memformulasikan pariwisata berkelanjutan untuk menciptakan kestabilan ekonomi, sosial dan lingkungan. Dalam mewujudkan pariwisata yang berkelanjutan, UNWTO memperkenalkan program volunterisme yang secara langsung menarik minat wisatawan dan membuat wisatawan semakin menyadari akan pentingnya menjaga lingkungan. Penelitian ini bertujuan untuk memahami strategi volunterisme untuk mewujudkan pariwisata berkelanjutan guna mengurangi sampah di lautan. Metode yang digunakan dalam penelitian ini adalah metode kualitatif-eksploratif yang menggali fenomena sosial berdasarkan variabel yang telah dirumuskan. Merespon isu polusi laut yang disebabkan oleh sampah, volunterisme menciptakan berbagai upaya untuk bekerja sama dengan para pemangku kepentingan. Program volunterisme yang berfokus pada topik polusi kelautan diharapkan mampu menjadi rekomendasi kebijakan yang dapat diimplementasikan oleh berbagai negara, sehingga upaya pengurangan sampah di lautan dapat secara masif dilakukan di berbagai bagian dunia yang berbeda. Studi ini mendiskusikan tentang penyebaran sampah di lautan dan upaya untuk menanganinya melalui program volunterisme. Kata-Kata Kunci: Limbah Lautan, Pariwisata Berkelanjutan, Volunterisme